ANALYSIS OF THE FACTORS THAT INFLUENCE THE PERFORMANCE OF EMPLOYEES OF REGIONAL OFFICE IN THE BARRU DISTRICT - Nur Fitri Aulia; Romansyah Sahabuddin; Abdul Rahim (SEAN Institute, 2023)
This study aims to 1) find out how much of the influence of the variable quality of human resources in the local government of Barru Regency. 2) find out how much influence the variable level of welfare has on the performance of local government employees in Barru Regency 3) know how much influence the variable work motivation has on the performance of local government employees in Barru Regency .4) find out how much influence the disciplinary variable has on local government employees in Barru Regency .5) find out how much influence the work ethic variable has on the performance of Barru Regency regional government employees. This type of research is quantitative research. Based on the source, the type of data used is primary data and secondary data. Data collection techniques used were interviews and documentation. The results of the research based on the F test show that the quality of human resources, the level of welfare, work motivation, discipline and work ethics jointly affect the performance of employees in the Barru Regency regional office. Meanwhile, based on the T test, the welfare level variable did not significantly influence the performance of Barru Regency regional office employees. In the variable quality of human resources, work motivation, discipline, and work ethics have a significant effect where the tcount is greater than the ttable value.